Analisis Tingkat Kepuasan Pengguna Jasa Terhadap Pelayanan dan Fasilitas Transportasi Bus Si Tayo (Studi Kasus: Koridor 1 Poris Plawad – Jatake) - Aldi ansyah (Civil Infrastructure Engineering and Architectural Design, 2026)
Based on previous studies and preliminary surveys of the Si Tayo Bus Corridor 1, it is known that several service aspects are still not in line with user expectations. Therefore, it is necessary to conduct an assessment to identify which performance indicators should be prioritized for improvement and to evaluate the current level of user satisfaction. This research employs the Importance-Performance Analysis (IPA), Customer Satisfaction Index (CSI), and SERVQUAL methods. In addition, a verification of the existing conditions in the field was also conducted. The data were collected using a Google Form questionnaire consisting of 15 service indicators categorized into the five SERVQUAL dimensions. A total of 100 valid responses were obtained and subsequently analyzed using the three methods. The results of the study indicate that there are two service indicators requiring immediate improvement, namely “bus arrivals and departures according to schedule” and “responsiveness of staff to passenger complaints.” Furthermore, it was found that the current user satisfaction level is 80.14%, which falls into the “satisfied” category. Field observations also confirmed that there are still two service indicators not meeting the expected standards, namely “bus arrivals and departures according to schedule” and the availability of real-time service information accessible to users.